# Sines and Cosines of Multiples or Submultiples

We will learn how to solve identities involving sines and cosines of multiples or submultiples of the angles involved.

We use the following ways to solve the identities involving sines and cosines.

(i) Take the first two terms of L.H.S. and express the sum of two sines (or cosines) as product.

(ii) In the third term of L.H.S. apply the formula of sin 2A (or cos 2A).

(iii) Then use the condition A + B + C = π and take one sine (or cosine) term common.

(iv) Finally, express the sum or difference of two sines (or cosines) in the brackets as product.

1. If A + B + C= π   prove that,

sin A + sin B - sin C = 4 sin $$\frac{A}{2}$$ sin $$\frac{B}{2}$$ cos $$\frac{C}{2}$$

Solution:

We have,

A + B + C = π

⇒ C = π - (A + B)

⇒ $$\frac{C}{2}$$ = $$\frac{π }{2}$$  - ($$\frac{A + B}{2}$$)

Therefore, sin ($$\frac{A + B}{2}$$) = sin ($$\frac{π }{2}$$  - $$\frac{C}{2}$$) = cos  $$\frac{C}{2}$$

Now, L.H.S. = sin A + sin B - sin C

= (sin A + sin B) - sin C

= 2 sin ($$\frac{A + B}{2}$$) cos ($$\frac{A - B}{2}$$) - sin C

= 2 sin ($$\frac{π - C}{2}$$) cos ($$\frac{A - B}{2}$$) - sin C

= 2 sin ($$\frac{π}{2}$$ -  $$\frac{C}{2}$$) cos $$\frac{A - B}{2}$$ - sin C

= 2 cos $$\frac{C}{2}$$ cos $$\frac{A - B}{2}$$ - sin C

= 2 cos $$\frac{C}{2}$$ cos $$\frac{A - B}{2}$$ - 2 sin $$\frac{C}{2}$$ cos $$\frac{C}{2}$$

= 2 cos $$\frac{C}{2}$$[cos $$\frac{A - B}{2}$$ - sin $$\frac{C}{2}$$]

= 2 cos $$\frac{C}{2}$$[cos $$\frac{A - B}{2}$$ - sin ($$\frac{π}{2}$$ -  $$\frac{A + B}{2}$$)]

= 2 cos $$\frac{C}{2}$$[cos ($$\frac{A - B}{2}$$) - cos ($$\frac{A + B}{2}$$)]

= 2 cos $$\frac{C}{2}$$[cos  ($$\frac{A}{2}$$ -  $$\frac{B}{2}$$) - cos  ($$\frac{A}{2}$$ + $$\frac{B}{2}$$)]

= 2 cos $$\frac{C}{2}$$ [(cos $$\frac{A}{2}$$  cos $$\frac{B}{2}$$ +  sin $$\frac{A}{2}$$  sin $$\frac{B}{2}$$) - (cos $$\frac{A}{2}$$  cos $$\frac{B}{2}$$ +  sin $$\frac{A}{2}$$  sin $$\frac{B}{2}$$)]

= 2 cos $$\frac{C}{2}$$[2 sin $$\frac{A}{2}$$   sin $$\frac{B}{2}$$]

= 4 sin $$\frac{A}{2}$$  sin $$\frac{B}{2}$$ cos $$\frac{C}{2}$$  = R.H.S.                    Proved.

2. If A, B, C be the angles of a triangle, prove that,

cos A + cos B + cos C = 1 + 4 sin $$\frac{A}{2}$$ sin $$\frac{B}{2}$$ sin $$\frac{C}{2}$$

Solution:

Since A, B, C are the angles of a triangle,

Therefore, A + B + C = π

⇒ C = π - (A + B)

⇒ $$\frac{C}{2}$$ = $$\frac{π }{2}$$  - ($$\frac{A + B}{2}$$)

Thus, cos ($$\frac{A + B}{2}$$) = cos ($$\frac{π }{2}$$  - $$\frac{C}{2}$$) = sin $$\frac{C}{2}$$

Now, L. H. S. = cos A + cos B + cos C

= (cos A + cos B) + cos C

= 2 cos ($$\frac{A + B}{2}$$)  cos ($$\frac{A - B}{2}$$)  + cos C

= 2 cos ($$\frac{π}{2}$$ - $$\frac{C}{2}$$) cos ($$\frac{A - B}{2}$$)  + cos C

= 2 sin $$\frac{C}{2}$$ cos ($$\frac{A - B}{2}$$) + 1 - 2 sin$$^{2}$$ $$\frac{C}{2}$$

= 2 sin $$\frac{C}{2}$$ cos ($$\frac{A - B}{2}$$) - 2 sin$$^{2}$$ $$\frac{C}{2}$$ + 1

= 2 sin $$\frac{C}{2}$$[cos ($$\frac{A - B}{2}$$)  - sin $$\frac{C}{2}$$] + 1

= 2 sin $$\frac{C}{2}$$[cos ($$\frac{A - B}{2}$$)  - sin ($$\frac{π}{2}$$ -  $$\frac{A + B}{2}$$)] + 1

= 2 sin $$\frac{C}{2}$$[cos ($$\frac{A - B}{2}$$)  - cos ($$\frac{A + B}{2}$$)] + 1

= 2 sin $$\frac{C}{2}$$ [2 sin $$\frac{A}{2}$$ sin $$\frac{B}{2}$$] + 1

= 4 sin $$\frac{C}{2}$$ sin $$\frac{A}{2}$$ sin $$\frac{B}{2}$$ + 1

= 1 + 4 sin $$\frac{A}{2}$$ sin $$\frac{B}{2}$$ sin $$\frac{C}{2}$$                    Proved.

3. If A +  B + C = π prove that,
sin $$\frac{A}{2}$$ +sin $$\frac{B}{2}$$ + sin $$\frac{C}{2}$$  = 1 + 4 sin $$\frac{π - A}{4}$$  sin $$\frac{π - B}{4}$$  sin $$\frac{π - C}{4}$$

Solution:

A + B + C = π

⇒ $$\frac{C}{2}$$ = $$\frac{π}{2}$$ - $$\frac{A + B}{2}$$

Therefore, sin $$\frac{C}{2}$$ = sin ($$\frac{π }{2}$$  - $$\frac{A + B}{2}$$)  = cos $$\frac{A + B}{2}$$

Now, L. H. S. = sin $$\frac{A}{2}$$ +sin $$\frac{B}{2}$$ + sin $$\frac{C}{2}$$

= 2 sin $$\frac{A + B}{4}$$ cos $$\frac{A - B}{4}$$ + cos ($$\frac{π}{2}$$ - $$\frac{C}{2}$$)

= 2 sin $$\frac{π - C}{4}$$ cos $$\frac{A - B}{4}$$ + cos $$\frac{π - C}{2}$$

= 2 sin $$\frac{π - C}{4}$$ cos $$\frac{A - B}{4}$$ + 1 – 2 sin$$^{2}$$ $$\frac{π - C}{4}$$

= 2 sin $$\frac{π - C}{4}$$  cos $$\frac{A - B}{4}$$ - 2 sin$$^{2}$$ $$\frac{π - C}{4}$$ + 1

= 2 sin $$\frac{π - C}{4}$$ [cos $$\frac{A - B}{4}$$  - sin $$\frac{π - C}{4}$$] + 1

= 2 sin $$\frac{π - C}{4}$$ [cos $$\frac{A - B}{4}$$  - cos {$$\frac{π}{2}$$  - $$\frac{π - C}{4}$$}] + 1

= 2 sin $$\frac{π - C}{4}$$ [cos $$\frac{A - B}{4}$$ - cos ($$\frac{π}{4}$$ + $$\frac{C}{4}$$)] + 1

= 2 sin $$\frac{π - C}{4}$$ [cos $$\frac{A - B}{4}$$ - cos $$\frac{π + C}{4}$$] + 1

= 2 sin $$\frac{π - C}{4}$$ [2 sin $$\frac{A - B + π + C}{8}$$  sin $$\frac{π + C - A + B}{8}$$] + 1

= 2 sin $$\frac{π - C}{4}$$ [2 sin $$\frac{A + C + π - B}{8}$$ sin $$\frac{B + C + π - A}{8}$$] + 1

= 2 sin $$\frac{π - C}{4}$$ [2 sin $$\frac{π - B + π - B}{8}$$ sin $$\frac{π - A + π - A}{8}$$] + 1

= 2 sin $$\frac{π - C}{4}$$ [2 sin $$\frac{π - B}{4}$$  sin $$\frac{π - A}{4}$$] + 1

= 4 sin $$\frac{π - C}{4}$$ sin $$\frac{π - B}{4}$$  sin $$\frac{π - A}{4}$$  + 1

= 1 + 4 sin $$\frac{π - A}{4}$$  sin $$\frac{π - B}{4}$$  sin $$\frac{π - C}{4}$$                    Proved.

4. If A + B + C = π show that,
cos $$\frac{A}{2}$$ + cos $$\frac{B}{2}$$ + cos $$\frac{C}{2}$$ =  4 cos $$\frac{A + B}{4}$$ cos $$\frac{B + C}{4}$$ cos $$\frac{C + A}{4}$$

Solution:

A + B + C = π

$$\frac{C}{2}$$ = $$\frac{π}{2}$$ - $$\frac{A + B}{2}$$
Therefore, cos $$\frac{C}{2}$$ = cos ($$\frac{π}{2}$$ - $$\frac{A + B}{2}$$) = sin $$\frac{A + B}{2}$$

Now, L. H. S. = cos $$\frac{A}{2}$$ + cos $$\frac{B}{2}$$ + cos $$\frac{C}{2}$$

= (cos $$\frac{A}{2}$$ + cos $$\frac{B}{2}$$) + cos $$\frac{C}{2}$$

= 2 cos $$\frac{A + B}{4}$$  cos $$\frac{A - B}{4}$$ +  sin $$\frac{A + B}{2}$$  [Since, cos $$\frac{C}{2}$$  = sin $$\frac{A + B}{2}$$]

= 2 cos $$\frac{A + B}{4}$$ cos $$\frac{A - B}{4}$$ + 2 sin $$\frac{A + B}{4}$$ cos $$\frac{A + B}{4}$$

= 2 cos  $$\frac{A + B}{4}$$[cos $$\frac{A - B}{4}$$ + sin $$\frac{A + B}{4}$$]

= 2 cos $$\frac{A + B}{4}$$ [cos $$\frac{A + B}{4}$$ + cos ($$\frac{π}{2}$$ - $$\frac{A + B}{4}$$)]

= 2 cos $$\frac{A + B}{4}$$ [2 cos $$\frac{\frac{A - B}{4} + \frac{π}{2} - \frac{A + B}{4}}{2}$$ cos  $$\frac{\frac{π}{2} - \frac{A + B}{4} - \frac{A - B}{4}}{2}$$]

= 2 cos $$\frac{A + B}{4}$$ [2 cos $$\frac{π - B}{4}$$ cos $$\frac{π - A}{4}$$]

= 4 cos $$\frac{A + B}{4}$$ cos $$\frac{C + A}{4}$$  cos $$\frac{B + C}{4}$$, [Since, π - B = A + B + C - B = A + C; Similarly, π - A = B + C]

= 4 cos $$\frac{A + B}{4}$$ cos $$\frac{B + C}{4}$$ cos $$\frac{C + A}{4}$$.                     Proved.

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

## Recent Articles

1. ### Arranging Numbers | Ascending Order | Descending Order |Compare Digits

Sep 15, 24 04:57 PM

We know, while arranging numbers from the smallest number to the largest number, then the numbers are arranged in ascending order. Vice-versa while arranging numbers from the largest number to the sma…

2. ### Counting Before, After and Between Numbers up to 10 | Number Counting

Sep 15, 24 04:08 PM

Counting before, after and between numbers up to 10 improves the child’s counting skills.

3. ### Comparison of Three-digit Numbers | Arrange 3-digit Numbers |Questions

Sep 15, 24 03:16 PM

What are the rules for the comparison of three-digit numbers? (i) The numbers having less than three digits are always smaller than the numbers having three digits as:

4. ### 2nd Grade Place Value | Definition | Explanation | Examples |Worksheet

Sep 14, 24 04:31 PM

The value of a digit in a given number depends on its place or position in the number. This value is called its place value.

5. ### Three Digit Numbers | What is Spike Abacus? | Abacus for Kids|3 Digits

Sep 14, 24 03:39 PM

Three digit numbers are from 100 to 999. We know that there are nine one-digit numbers, i.e., 1, 2, 3, 4, 5, 6, 7, 8 and 9. There are 90 two digit numbers i.e., from 10 to 99. One digit numbers are ma